(untitled) (Journal of the College of Education for Women, 2019)
Wadi AL – yabis situated to the north jorden , its extended from Aglonmountain to the jorden river , the surveying of this valley about 186 KM , and thehighest point in it about 1200 m upon the sea level , the lower point ther under thesea level . This study lay to appear the historical important and to study the variationof environment and population which happened in the different periods , in thebeginning the Paleolithic until the later period , and to understand the environment ,political and economical circumstances , which it can to influenced or limited inhuman behavior from choosing , the settlement sits and than ( we could ) knowledgeof living ways and the tools which they used in there living and show thearchitectural ways.About the name of this valley which nominated in this name which related tosome one his name ( yabis ) and this name didn’t refer to disappeared the plantationsin it , and it is recently name of this valley is AL – Rayan valley .The important historical period which found some settlement relics in thisvalley a1. pre pottery Neolithic A and B2. chalcolithic ( 3750 – 3200 B.C )3. Bronza Age ( 3200 – 1200 B.C )4. Iron Age ( 1200 – 586 B.C )5. Bersian and Hellenistic Age ( 539 – 64 B.C )6. Roman Age ( 64 B.C – 333 A.D )7. Byzantine Age ( 333 – 635 A.D )8. Islamic and Modern Ages ( 635 A.D )After the first war world , ( this valley ) abandoned because nomadic attic uponthis sites , in addition abandoned almost of that sites which in this valley .The most important sites which excavated there are AL – Raheb site in Arjan ,Iraq AL – Dubb site , Tell EL – Meqbereh and Kurkuma site , they are found in itsome material relics which go back to that period above .The population of these villages depended upon the plantations(essentially ) because much heavy rain and well available like Ean – AL – bedha ,Ean – AL – tanor and others scatter in the valley .The population of this valley buried there dead under the house floors in earlierperiods and than in the cemetery out site , the villages in different situationsaccording to what known in the Near Eastern countries .